Identification and Characterization of a Non-muscular Myostatin in the Nile Tilapia - Segev-Hadar, Adi; Alupo, Gertrude; Tal, Kfir; Nitzan, Tali; Biran, Jakob (Frontiers in Endocrinology, 2020)
The growth and differentiation factor Myostatin (MSTN, also known as GDF8) negatively regulates skeletal muscle development and growth in vertebrates. Most fish genomes contain two or more mstn genes, which are expressed in muscle and other tissues. Yet, in the genome of Nile tilapia (Oreochromis niloticus), which is one of the world’s most important aquaculture fish species, only one mstn gene has previously been identified. Here, we identify a second mstn gene in Nile tilapia. We show that it clusters phylogenetically with other piscine mstn2 genes and that it shares chromosomal synteny with the human and zebrafish orthologs. We further show that mstn2 is not expressed in red or white muscles of Nile tilapia, but rather that its main site of expression is the brain. To determine which physiological functions are correlated with mstn expression, adult Nile tilapia were exposed to various environmental conditions and their effect on mstn1 and mstn2 expression in the brain and muscles was measured using real-time PCR. We found that the centrally- and muscle-expressed mstn genes differ in their responsiveness to diverse challenges, suggesting differential gene- and tissue-specific regulation of their expression. Metabolic and stress marker analyses showed that the altered mstn expression is not regulated by classical stress response. Taken together, our findings expand the understanding of the MSTN system in Nile tilapia and provide evolutionary insight into its function.